(untitled) (Research, Society and Development, 2021)
The objective of the present research was to evaluate the degree of knowledge of parents of children living in the municipality of Mirassol D’Oeste about intestinal parasites and the possible ways of contamination. A cross-sectional study was carried out with descriptive statistics and analysis of qualitative data that, through a questionnaire, was based on the understanding, experience or knowledge of parents or guardians of 60 children up to thirteen years old about intestinal parasites. Most parents and guardians of the children, 45%, have higher education; 76.67% use well water for consumption; 81.67% have public garbage collection; 80% of respondents answered to know what is intestinal parasite; 78.33% know how to recognize when the child is parasitized; 88.67% have already taken antiparasitic medicine and 85% reported that children wash their hands before meals. This study shows that the studied population has basic knowledge about intestinal parasites, which may reflect the level of education and access to information on the subject. Most interviewees know how to identify symptoms, perform stool tests on children and use antiparasitic drugs. Our results demonstrate that access to information and knowledge about intestinal parasites is the greatest preventive measure against infections. Thus, there is an evident need to further expand access to information, whether through social networks, podscast, educational videos, lectures, leafleting, home visits, to cover the whole community, raising hygiene and self-care levels and decreasing infection rates.